Perancangan Stasiun Isi Ulang Air Minum BXCan - Elvaretta, Bella; Sugianto, Donna Angelina (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2023)
The existence of public facilities in the Mal aims to provide convenience and satisfaction for Mal visitors. BXC Park is a public space facility used by visitors as a place to exercise and relax. Activities carried out by visitors at BXC Park tend to be draining so that the body will feel thirsty and need fluid intake. However, there is no access for visitors to get drinking water in the BXC Park area. This research was created to provide solutions to the problems experienced by BXC Park visitors so that sports activities become more effective. The method used in carrying out this research begins with observing the problems found in BXC Mal, identifying BXC Mal visitor activities, and in the final stage is determining what kind of tools can facilitate access for Mal visitors to get drinking water after exercising. The final result obtained is to design a BXCan drinking water refill station that complies with post-pandemic standards.